2017
DOI: 10.1371/journal.pone.0182025
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics profiles in rats with acute traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a major cause of mortality and disability worldwide. We validated the utility of plasma metabolomics analysis in the clinical diagnosis of acute TBI in a rat model of controlled cortical impact (CCI) using gas chromatography/mass spectrometry (GC/MS). Thirty Sprague-Dawley rats were randomly divided into two groups of 15 rats each: the CCI group and sham group. Blood samples were obtained from the rats within the first 24 h after TBI injury. GC/MS measurements were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
2
14
0
1
Order By: Relevance
“…TRPV4 is also activated by 5', 6'-epoxyeicosatrienoic acid [44], which is a signaling molecule formed in various cell types via metabolism of arachidonic acid. Arachidonic acid is upregulated in the brain in response to traumatic brain injury [47]. OPCs proliferate in response to CNS injury [28], and this may be mediated by stimulation of TRPV4 via arachidonic acid metabolites during brain inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 is also activated by 5', 6'-epoxyeicosatrienoic acid [44], which is a signaling molecule formed in various cell types via metabolism of arachidonic acid. Arachidonic acid is upregulated in the brain in response to traumatic brain injury [47]. OPCs proliferate in response to CNS injury [28], and this may be mediated by stimulation of TRPV4 via arachidonic acid metabolites during brain inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…metabolism, amino acid metabolism, galactose metabolism, and arachidonic acid metabolism were disturbed in the plasma of rats subjected to TBI 18 . Another study revealed a decrease of citrate and aconitate in TBI patients' plasma amongst other disturbed metabolites 17 .…”
mentioning
confidence: 95%
“…Metabolomic studies provide comprehensive information on various in vivo enzymatic activities and have been successfully applied to obtain disease markers in neurodegenerative pathologies. TBI metabolomic marker characterization have been performed using Nuclear Magnetic Resonance (NMR) (Bahado-Singh, 2016b; Glenn et al, 2013; Robertson et al, 2013; Viant et al, 2005), or Mass Spectrometry (MS) of lipids (Emmerich et al, 2016; Emmerich et al, 2017; Sheth et al, 2015), targeting smaller and specific classes of metabolites or liquid chromatography/mass spectrometry (LCMS) based metabolomics, targeting broader biochemical changes (Bahado-Singh, 2016a; Daley, 2016; Oresic et al, 2016; Yi et al, 2016; Zheng et al, 2017). In order to target a wide range of metabolites in the developing brain, we performed LC-MS based brain tissue metabolomics in a preclinical rat model subjected to a fluid percussion TBI.…”
Section: Introductionmentioning
confidence: 99%